Third-Party Loan Guarantees: Measuring Literacy and its Effect on Financial Decisions - Elisabeth Beckmann; Christa Hainz; Sarah Reiter (Oesterreichische Nationalbank (OeNB), 2022)
Granting a third-party guarantee for a loan does not directly involve a financial transaction. Therefore, guarantors might not understand that they are taking on a liability, albeit contingent. We introduce literacy about guarantees as a novel and distinct aspect of financial literacy. For ten Eastern European countries, we find that 45 percent of individuals lack this form of financial literacy. Instrumenting individual guarantee literacy with regional cohort-specific financial literacy, we show that guarantee literacy significantly reduces the probability of acting as a guarantor. Our results are robust to a placebo analysis and several sensitivity checks.
Keywords: D14; G51; G53; 330; Third-party loan guarantees; guarantee literacy; financial literacy; IV